Financial crises, macroeconomic variables, and long-run risk: An econometric analysis of stock returns correlations (2000 to 2019) - Marco Tronzano (Journal of Risk and Financial Management, 2021)
This paper focuses on four major aggregate stock price indexes (SP 500, Stock Europe 600, Nikkei 225, Shanghai Composite) and two "safe-haven" assets (Gold, Swiss Franc), and explores their return co-movements during the last two decades. Significant contagion effects on stock markets are documented during almost all financial crises; moreover, in line with the recent literature, the defensive role of gold and the Swiss Franc in asset portfolios is highlighted. Focusing on a new set of macroeconomic and financial series, a significant impact of these variables on stock returns correlations is found, notably in the case of the world equity risk premium. Finally, long-run risks are detected in all asset portfolios including the Chinese stock market index. Overall, this empirical evidence is of interest for researchers, financial risk managers and policy makers.
Keywords: C22; G15; 330; DCC model; financial risk management; international financial markets co-movements; safe-haven assets; stock prices